Influences of Saturation and Wetting-Drying Cycle on Mechanical Performances of Argillaceous Limestones from Liupanshan Tunnel, China - Bo Meng; Hongwen Jing; Wenxin Zhu; Haijian Su (Advances in Materials Science and Engineering)
Water-rock interaction is a vital factor to affect the stabilities of rock projects. This paper conducted a series of experiments on argillaceous limestones to investigate the influences of saturation and wetting-drying cycle on the physical and mechanical performances of rocks. The results show that the increasing saturation increases the dissolution of clay minerals and lubrication among mineral grains, resulting in an obvious reduction effect on the strength and deformation performances of argillaceous limestones. Wetting-drying cycle increases the porosity and changes the pore structure of argillaceous limestones, leading to the pore transformation from small pore (0.01∼0.1 μm) to relatively large pore (0.1∼1.0 μm). Both the physical and mechanical performances of argillaceous limestones are weakened by the wetting-drying cycle. Besides, the variation process of the physical and mechanical parameters, including mass loss, density, ultrasonic velocity, compression strength, peak strain, elasticity modulus, and secant modulus, can be divided into two stages: 0∼6th wetting-drying cycle, gently changing, and 6th∼12th wetting-drying cycle, drastically changing. The whole change process of these physical and mechanical parameters with the increase in the wetting-drying cycle number can be expressed with the exponential function in general.